2012
DOI: 10.4067/s0717-95022012000100024
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study on the Psoas Minor Muscle in Human Fetuses

Abstract: SUMMARY:The anatomy of the psoas minor muscle in human beings has frequently been correlated with ethnic and racial characteristics. The present study had the aim of investigating the anatomy of the psoas minor, by observing its occurrence, distal insertion points, relationship with the psoas major muscle and the relationship between its tendon and muscle portions. Twenty-two human fetuses were used (eleven of each gender), fixed in 10% formol solution that had been perfused through the umbilical artery. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…During an examination of 22 fetuses, Guerra, et al described fanlike expansions coming from the tendon of the PMM that joined the fascia of the psoas major muscle [2]. This suggests that psoas accessories could indeed be due to an incomplete separation between the psoas major and minor muscles during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…During an examination of 22 fetuses, Guerra, et al described fanlike expansions coming from the tendon of the PMM that joined the fascia of the psoas major muscle [2]. This suggests that psoas accessories could indeed be due to an incomplete separation between the psoas major and minor muscles during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PSMI was reported 9% in black adult men and 96% in white adult men [12]. In their study on fetuses, Guerra et al, Reis, Bastos, & Brito [13] found out that the muscle was present in 59,09% of the subjects. Moreover, there are some other studies in literature reporting the fact that race and gender differences may affect the presence of the muscle [12,14].…”
Section: Introductionmentioning
confidence: 90%
“…In the present study, tendon, in all the cases, was long, flattened out at insertion and blended with iliopsoas fascia; some aponeurotic fibres inserting over iliopectineal line (Fig.3a.). Guerra et al (2012) 8 have reported the presence of Psoas minor muscle in 13/22(59%), of which, in 4 fetuses Psoas minor tendon passed posteriorly to the crural arch & then into the pectineal line of femur. In the present study conducted on adult cadavers, it is found in 40%cases.…”
Section: Observationsmentioning
confidence: 99%
“…7 As quoted by Guerra et al (2012) 8 , in 1988 Gardener et al 9 reported its insertion by a thin tendon, into iliopectineal eminence and arcuate line, inconstant insertion into iliac fascia and pectineal ligament. Further, Guerra et al (2012) 8 have stated that according to Testut and Latarjet (1976) 10 , it is not rare to find this muscle reduced to one or two tendons. Hence the present study has been undertaken to review the morphology of this vestigial, yet significant muscle.…”
Section: Introductionmentioning
confidence: 99%